Attenuation Acute Effects of Passive Smoking on Pulmonary Tissues in Rats by Bee Honey - Alshailabi, Eda M.A.; Al-Zail, Nura I.; Alsalhin, Afaf A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The recent study’s goal was to use honey to reduce the acute effects of passive smoking on rats’ pulmonary tissues. A total of 28 adult male rats were categorized into four groups: (1) control group; (2) rats were given honey (100 mg/kg BW/30 days); (3) rats were exposed to the cigarette smoke for 30 days; and (4) rats were given honey (100 mg/kg BW/14 days); previously, the rats were exposed to cigarette smoke for 30 days. The mean Wet/Dry values were significantly higher in the KAR group than in the NC rats. While the PTV rats showed a notable decline in comparison to the KAR rats, the PTV rats showed no change with the NC rats. Also, after 30 days of exposure to KAR, we observed numerous changes in the rats’ gross lung lesions and more histological alterations as compared to all other rats’ lungs. Furthermore, the lung tissue of the PTV rats had some histological changes and a moderate improvement in tissue structure when compared to KAR rats. In conclusion, the study demonstrated the beneficial effects of honey in lowering lung tissue damage. It is also a better treatment choice, which may lead to better results in terms of tissue damage caused by CS.